2021
DOI: 10.3390/vaccines9040316
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Neutralizing Activity Comparison of SARS-CoV-2 Spike Full-Length and Subunit Domain Proteins in Young Adult and Old-Aged Mice

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be expanding the pandemic disease across the globe. Although SARS-CoV-2 vaccines were rapidly developed and approved for emergency use of vaccination in humans, supply and production difficulties are slowing down the global vaccination program. The efficacy of many different versions of vaccine candidates and adjuvant effects remain unknown, particularly in the elderly. In this study, we compared the immunogenic properties of SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Previous report showed that the SARS-CoV-2 S1 subunit protein can stimulate the SARS-CoV-2 S1-specific IgG titer higher than the SARS-CoV-2 RBD protein when using the SARS-CoV-2 S1 protein and SARS-CoV-2 RBD protein as a coating antigen in ELISA [28]. Further, alum adjuvant can enhance the Th-2 (IgG1) immune response better than the Th-1 (IgG2a) immune response [45], which confirmed in the present study that the SARS-CoV-2 RBD-specific IgG1 antibody responses were increased more than the SARS-CoV-2 RBD-specific IgG2a antibody responses [27,45].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous report showed that the SARS-CoV-2 S1 subunit protein can stimulate the SARS-CoV-2 S1-specific IgG titer higher than the SARS-CoV-2 RBD protein when using the SARS-CoV-2 S1 protein and SARS-CoV-2 RBD protein as a coating antigen in ELISA [28]. Further, alum adjuvant can enhance the Th-2 (IgG1) immune response better than the Th-1 (IgG2a) immune response [45], which confirmed in the present study that the SARS-CoV-2 RBD-specific IgG1 antibody responses were increased more than the SARS-CoV-2 RBD-specific IgG2a antibody responses [27,45].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the receptor binding domain (RBD) from the S1 subunit induced significant immune response and neutralizing antibodies which were evident from several studies [14,15]. The full length of the S1 subunit also can stimulate the immune response and the neutralization antibodies to block the viral infection [27][28][29]. As a result, the S1 subunit in the S protein could be a target for developing an effective SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of SARS-CoV-2 vaccines there have been numerous adjuvants that have shown beneficial effects on immunogenicity [46][47][48][49] . Interestingly, a AS01-like adjuvanted SARS-CoV-2 subunit vaccine enhanced Th1-type IgG2a isotype and IFN-γ secreting T cell immune responses in BALB/c mice when compared to unadjuvanted control 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, AS03-adjuvanted CoV2 preS dTM (B.1.351) induced higher neutralizing antibody titers against Beta variant in non-human primates compared to animal group boosted with non-adjuvanted vaccine in the mRNA-primed cohort [21]. AS01-like adjuvanted SARS-CoV-2 subunit vaccine enhanced Th1 type-IgG2a isotype, neutralizing antibodies, and IFN-γ secreting T cell immune responses in both young and aged mice [45]. Recombinant S protein in combination with adjuvant CoVaccine HT™ induced a balanced IgG subtype antibody response [41].…”
Section: Discussionmentioning
confidence: 99%